Pooh's Christmas sled ride - Gaines, Isabel; Milne, A. A. (Alan Alexander), 1882-1956.; Studio Orlando (New York : Random House, 2003)
Piglet keeps falling off the sled before the friends from the Hundred Acre Wood even start down the big hill, and they try various ways to keep him aboard before finding one that works.
"Based on the "Winnie the Pooh" works by A.A. Milne and E.H. Shepard."
"Based on the "Winnie the Pooh" works by A.A. Milne and E.H. Shepard."
Keywords: Sledding -- Fiction; Pigs -- Fiction; Toys -- Fiction; Animals -- Fiction